. Patient community as a factor in the development of medical education practices in modern Russia - A. G. Miroshnichenko; L. G. Smyshliaeva; T. D. Podkladova; I. I. Soshenko; A. O. Okorokov (Russian State Vocational Pedagogical University, 2022)
Introduction. The study draws attention to the need to transform the Russian system of medical education. It is connected with overcoming modern challenges and Russia's focus on improving the quality of life of people as a key state priority. The authors substantiate the connection of the patient-centred approach with the values of the "anthropological turn" in the field of medical education. The results of the analysis of foreign experience in the implementation of patient-oriented pedagogical focus in the practices of medical education are given. The study analyses the cases related to the peculiarities of patient communities functioning in order to identify their possible influence on the development of medical education practices.Aim. The current research aimed to identify ways and conditions of using the opportunities of patient communities for the development of practices of Russian medical education.Methodology and research methods. System-based, activity-oriented and phenomenological approaches made up the methodology of the study. Research methods: theoretical analysis, phenomenological analysis, structural analysis, survey, Delphi technique, focus group.Results. The research results are the following:The main directions for the development of medical education practices in the patient-oriented paradigm were outlined, namely: the formation of new, defined in terms of polysubjectivity (students, teachers, practitioners, representatives of patient communities) ways of organising educational interaction; transformation of didactic characteristics of medical academic programmes; updating the forms and means of work to form the worldview of future doctors within the framework of humanistic values.The study revealed the features of the educational functionality of patient communities, which is significant for the development of medical education practices, shown through the following roles of patient community: diagnostician, content developer, designer, moderator, mediator, researcher, analyst, technologist, teacher (trainer), expert. The revealed roles allowed the authors to identify patient community as an actor in the development of modern Russian medical education practices.The organisational and pedagogical ways of patient community influence on the development of medical education were identified: interactive polysubject collaboration of pedagogical, medical and patient communities in the design and implementation of academic programmes; organisation of open design-reflective communication platforms for discussing topical problems of patient communities with the involvement of subjects of medical education; volunteer projects integrating the activity of patient communities and students of medical academic programmes.The study identified the conditions for using patient communities for the development of education practices and professional development of a modern physician, including: well-established organisational and methodological mechanisms for the implementation of roles of the patient community in the organisation of all didactic components of the educational process (its types) in the system of continuous professionalisation of physicians (objectives, content, teaching technologies, monitoring of educational results); availability of systemically functioning mechanisms for introducing students of medical academic programmes to the practices of medical communities.Scientific novelty. The study substantiates the expediency of the interaction of the professional and educational medical communities with the patient as a factor in the development of the Russian system of medical education within the framework of a patient-oriented paradigm that reflects the values of the anthropological turn.The study reveals the types of activities of patient communities. These types reflect their identity as a new actor in the development of Russian medical education practices, namely: communicative, informational, project, expert, and diagnostic; evidence-based motivation for change.The authors prove the potential of the patient community as an actor in the development of Russian medical education practices, the implementation of which is ensured by creating organisational and pedagogical conditions that actualise these communities as the subjects of the educational process through multifaceted and functionally defined roles.The study outlines the ways and conditions of using the potential of polysubject interaction (patient, professional and educational medical communities) to transform the basic didactic characteristics of the educational process (its variations) in the medical education system.Practical significance. The obtained scientific results can be used to develop the content and activity-technological formats of educational programmes of higher medical education, to enrich practices of continuous medical education, to expand the productive experience of interaction between patient, medical and educational communities.